Examining the relationship between speaking anxiety in English and overall English proficiency among ELS undergraduates in UKM - Siti Zahidah Zahra Mohd Zamri,; Fuzirah Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Malaysian undergraduates generally have a significant deficiency in English proficiency, which is concerning for the next generation. This is despite the fact that they are exposed to English since kindergarten or primary school. Many Malaysian undergraduates struggle with English, which is their second language. Feeling worried about perceptions of others could be the contributing factor to students being anxious to speak in English, resulting in second language anxiety. Thus, it is the objective of this study to examine the relationship between English speaking anxiety and overall English proficiency level among English Language Studies’ undergraduates. Besides, the study also investigated the factors that contributed to their speaking anxiety in English. 80 undergraduates from a public university have been selected to participate in the study. The data collection was executed using a questionnaire, and the data was analyzed by utilizing the Statistical Package for the Social Sciences (SPSS) software, which allows a detailed statistical data analysis. In relation to this, this study will report on findings obtained from the analysis to discuss the levels of speaking anxiety and how second language speaking anxiety correlate with English proficiency level.